The practice of hiring, training and promoting less-educated workers in Malaysian-based manufacturing companies - Mohd Yunus, Azmir; Bakar, Ab. Rahim; Hamzah, Azimi; Wan Jaafar, Wan Marzuki (Canadian Center of Science and Education, 2016)
his paper reports a qualitative study on the experience of Malaysian employers in hiring, training, and promoting workers with low levels of formal education. Data for this study were obtained from interviews with six individuals who have experience in hiring and supervising less-educated workers. They are managers and executives from three different manufacturing companies: a fabric company, a steel company, and an automotive company. The findings show that less-educated workers are hired for entry-level jobs because they are less demanding and are more likely to stay at the same company for a longer period of time. To compensate for the workers’ lack of education, the employers provide learning opportunities, mostly through on-the-job training. Lack of education is not a barrier to career progression at these companies, because workers are promoted based on performance rather than qualifications.